Book review: Krizsán, A. & Roggeband, C. (2021). Politicizing Gender and Democracy in the Context of the Istanbul Convention. Palgrave MacMillan. - Gilby, Lynda (Intersections. East European Journal of Society and Politics, 2022)
The Council of Europe Convention on Violence Against Women and Domestic Violence, commonly referred to as ‘the Istanbul Convention,’ came into force in 2014, and is one of the most extensive legal and policy instruments on tackling violence against women (p. 2). However, opposition to the Istanbul Convention has become a focal point of broader opposition to gender equality in the European Union. This book explores the emergence and dynamics of this opposition. It investigates its implications for policies combating violence against women and contributes to scholarship of social movements, particularly their transnational qualities and their interaction with opponents and the state.